A aceitação na relação terapêutica e sua fundamentação fenomenológica existencial - Perosa, Miguel Angelo Yalenti (2022)
This thesis´s objective was to present the conceptualization and the existential phenomenological foundation of acceptance in the therapeutic relationship. It began with a theoretical introduction explaining the main Heideggerian phenomenologicalexistential concepts, a philosophical approach that was used in the foundation of acceptance in therapeutic context. Then, a daseinsanalyse therapy objective and method explanation was made, and was showed how the daseinsanalyse´s method presupposes a hall of attitudes that build the Therapeutic Setting. Thus, after, this thesis sought to clarify what the Therapeutic Setting is and carried out an analysis of acceptance, one of its components, demonstrating the Heideggerian foundations for it. To exemplify how acceptance is present in clinical practice, six sessions of daseinsanalytic therapy were presented, in which an analysis of this therapeutic approach was made. We tried to show that the clinical method of daseinsanalysis is the same hermeneutic daseinsanalytic method for research; and therefore, the six sessions were presented as examples of the clinical and research method practice. Finally, a final reflection was presented, in which a synthesis of this thesis object was configured, evidencing the author's motivation, his specific contribution to the daseinsanalytic therapist training knowledge and to whom it may be useful. It is also clear the idea that the points presented do not refer to more than a small part in the construction of daseinsanalytic method knowledge, as a permanent and interminable achievement